Implementasi Kebijakan Penyelenggaraan Pelelangan Ikan di Kota Ambon - Renita Buton; Rugaya Al-Hamid; Hengky Virgo R Pattimukay (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to analyze the Implementation of Fish Auction Implementation Policy in Ambon City. Fish auction place (TPI) is one of the main functions in fisheries activities which is also one of the driving factors in improving the welfare of fishermen. This type of research is a qualitative research that aims to find out the implementation of Fish Auction Implementation Policy in Ambon City based on the problems discussed, namely the problems that occur at the research location. The informants in this study were 13 people. Data collection was done by interview, observation and documentation. Data analysis through data reduction, data presentation and conclusion drawing, while data validity uses triangulation of sources, techniques and time. The results showed that the implementation of the policy of organizing fish auctions in Ambon City was not optimal because of the interests that occurred more to personal interests, lack of facilities, the role of implementers/staff who were less effective.